PHYSICAL PERCULARITIES OF HETEROSTRUCTURED SOLAR PHOTOELEMENTS - Yuldashev, Ulugbek (Мир исследований, 2021)
The thermonuclear energy is the primary source of all energy resources on Earth; coal, oil, gas; hydropower; wind and ocean energy. The sun is the source of all energy on earth. Solar power photoelement cells with the help of sunlight settling energy carrier into a high-temperature thermal energy source. Typically, each of these cells will be heterostructure and the efficiency coefficient is 9%. In this study, the efficiency of a heterostructured solar cell photocell was calculated.